Analyzing Direct And Indirect Speech Acts In “Up” Children Movie - Elvandari Maulana (DIMAR: Jurnal Pendidikan Islam, 2020)
This study aims at analyzing direct and indirect speech acts uttered by children in “UP” children movie. It is focused on character Russell since he is the main character who plays role as a child. This study is descriptive qualitative study where the result is not computed in statistical formula but in the form of strings of words. After analyzing the data, the results show that direct speech acts are dominant uttered by character Russell. It can be concluded that children tend to use direct speech acts especially in giving statement or information since their characteristics is they want to be looked as the great people.